2006
DOI: 10.1111/j.1365-2648.2006.03785.x
|View full text |Cite
|
Sign up to set email alerts
|

Keeping close: mothering with serious mental illness

Abstract: To assist mothers with serious mental illness, healthcare professionals must be sensitive to the social and cultural context in which they mother in order to create healthier possibilities for nurturing their children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(131 citation statements)
references
References 31 publications
6
121
0
4
Order By: Relevance
“…Although it cannot be certain that midwives consciously conveyed and created an atmosphere of surveillance and scepticism in their interactions with women, the feeling of being observed and watched as they cared for their baby was reported by some women and reflects previous research findings in this area (Hendrick and Daly, 2000, Montgomery et al, 2006, Davies and Allen 2007. The interactions between women and midwives may have been informed by an iterative process occurring between the possible mediating factor of women's self-stigmatisation, and their negative self-perception of their ability to care for their babies to the best of their ability, and midwives' surveillance behaviour.…”
supporting
confidence: 57%
“…Although it cannot be certain that midwives consciously conveyed and created an atmosphere of surveillance and scepticism in their interactions with women, the feeling of being observed and watched as they cared for their baby was reported by some women and reflects previous research findings in this area (Hendrick and Daly, 2000, Montgomery et al, 2006, Davies and Allen 2007. The interactions between women and midwives may have been informed by an iterative process occurring between the possible mediating factor of women's self-stigmatisation, and their negative self-perception of their ability to care for their babies to the best of their ability, and midwives' surveillance behaviour.…”
supporting
confidence: 57%
“…Previous research has highlighted that mothers with mental illness frequently experience stigma and judgement both from society and their families, and are frequently perceived as 'incompetent' mothers (Edwards and Timmons 2005;Krumm and Becker 2006;Davies and Allen 2007). As Montgomery (2006) points out, mental illness presents a challenge to the established stereotypical image of the ideal mother. The current study revealed a refreshing insight that the women participants seemed to be generally positive about disclosing their mental illness diagnoses at their booking appointment.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…86 Furthermore, the literature on mothers with mental illness indicates that health care providers should pay particular attention to ensuring that these women receive the necessary care for themselves as they are likely to put the needs of their children before their own. 89,90 For some mothers with mental illness, putting their children's needs before their own affirms their role as mothers and allows them to feel "normal" and close to their children. 90 As a result, some mothers choose not to take their medication or choose caring for their children over their own mental health care, 89,90 which has the potential to precipitate a deterioration in mental health and may ultimately result in hospitalization.…”
Section: Implications For Behavioral Healthmentioning
confidence: 97%
“…89,90 For some mothers with mental illness, putting their children's needs before their own affirms their role as mothers and allows them to feel "normal" and close to their children. 90 As a result, some mothers choose not to take their medication or choose caring for their children over their own mental health care, 89,90 which has the potential to precipitate a deterioration in mental health and may ultimately result in hospitalization. 91 This is precisely the outcome that many mothers with mental illness fear most, as they perceive that inpatient treatment will increase their risk of losing their children to family members or to the child welfare system.…”
Section: Implications For Behavioral Healthmentioning
confidence: 97%